NAIK TURUNNYA KINERJA PEGAWAI NON MEDIS DITINJAU DARI KOMPETENSI DAN DISIPLIN KERJA PADA RS. WONOLANGAN PROBOLINGGO - Saiful Bahri; Novita Eka Rista; Tumini Tumini (Universitas Bina Taruna Gorontalo, 2024)
Performance is a factor of concern for all organizations, because performance will be used as a measure of whether the organization is successful or not in its management. Many factors can influence the performance of each employee, including competency and work discipline. Likewise, Wonolangan Hospital wants all of its employees to have high performance. Based on the results of research on non-medical employees at Wonolangan Hospital, it was found that employee competence and work discipline have a positive and significant effect on employee performance. This is shown through the calculated t coefficient of competence and work discipline showing a coefficient that is greater than the t table coefficient with a smaller probability level. from the alpha value, namely 0.05. Together these two variables have a positive and significant effect and variations in the performance of non-medical employees at Wonolangan Hospital are 62.4% influenced by the rise and fall of employee competence and work discipline, therefore Wonolangan Hospital management must pay attention to how to improve the competence and work discipline of Wonolangan Hospital employees. Performance is a factor of concern for all organizations, because performance will be used as a measure of whether the organization is successful or not in its management. Many factors can influence the performance of each employee, including competency and work discipline. Likewise, Wonolangan Hospital wants all of its employees to have high performance. Based on the results of research on non-medical employees at Wonolangan Hospital, it was found that employee competence and work discipline have a positive and significant effect on employee performance. This is shown through the calculated t coefficient of competence and work discipline showing a coefficient that is greater than the t table coefficient with a smaller probability level. from the alpha value, namely 0.05. Together these two variables have a positive and significant effect and variations in the performance of non-medical employees at Wonolangan Hospital are 62.4% influenced by the rise and fall of employee competence and work discipline, therefore Wonolangan Hospital management must pay attention to how to improve the competence and work discipline of Wonolangan Hospital employees.